2021
DOI: 10.1051/0004-6361/202142022
|View full text |Cite
|
Sign up to set email alerts
|

Semi-regular red giants as distance indicators

Abstract: Context. Semi-regular variables (SRVs) are similar to Miras in brightness, and they also follow one or more period–luminosity relations (PLRs), though not necessarily the same one as Miras. As potential standard candles they are more challenging than Miras because of their smaller variability amplitudes and less regular light curves, but they are substantially more numerous and especially promising for probing old stellar populations. Aims. We aim to characterise the variability of SRVs, specifically focusing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…(2017, and references therein; see also Trabucchi et al 2021a), we are able to identify the pulsation mode responsible for each period. We identify nine sources with a period due to the fundamental mode, eight sources pulsating predominantly in the first-overtone mode, and one star (S1 * 338) whose period is most likely due to pulsation in the second-overtone mode.…”
Section: Analysis Of the Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…(2017, and references therein; see also Trabucchi et al 2021a), we are able to identify the pulsation mode responsible for each period. We identify nine sources with a period due to the fundamental mode, eight sources pulsating predominantly in the first-overtone mode, and one star (S1 * 338) whose period is most likely due to pulsation in the second-overtone mode.…”
Section: Analysis Of the Resultsmentioning
confidence: 95%
“…However, it should be noted that the traditional distinction between Miras and semiregular variables, according to which the former have visual amplitude ΔV > 2.5 mag, has been criticized by a number of studies (e.g., Kerschbaum & Hron 1992;Kiss et al 2000;Lebzelter & Hinkle 2002). Recently, Trabucchi et al (2021a) have shown that semiregular variables in the LMC that pulsate only in the fundamental mode follow the same sequence as Miras both in the PLD and in the period-amplitude diagram, suggesting that it would be incorrect to assign them different variability types only because their amplitude is smaller than an arbitrary, although reasonable, threshold.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…Therefore, the reliability of the distances derived with this method can be arguable. More recently, Trabucchi et al (2021) investigated the suitability of SRs as distance indicators and found that a subgroup of SRs follows the same sequence as Mira variables in the PL diagram. However, they concluded that long-time series are necessary to properly classify SRs according to their pulsation periods.…”
Section: A New Distance Cataloguementioning
confidence: 99%
“…Physically they are often linked with high-amplitude fundamental mode pulsation and hence membership of a particular period-luminosity sequence. From an observational perspective, this definition is often approximated as a pure amplitude cut (e.g Soszyński et al 2013) although Trabucchi et al (2021) acknowledge that this simple consideration removes lower amplitude stars on the same fundamental period-luminosity relation as the higher amplitude systems. In the M09 analysis, stars are considered as non-Mira variables if the amplitude in any of J, H or K s is less than 0.4 although this removes only ∼ 10 per cent of the stars in their sample.…”
Section: Light Curve Modellingmentioning
confidence: 99%